POLYETHERETHERKETONE (PEEK) SEBAGAI CENGKRAM GIGI TIRUAN SEBAGIAN LEPASAN - Fransiska Nuning Kusmawati (Universitas Baiturrahmah, 2021)
Introduction: Clasp is an important component in a removable partial denture. Conventional clasps are usually made of metal alloys. The patient usually refuses to have a metal clasp due to the unaesthetic color that affects their appearance. This article aims to determine the types of clasps other than those made of metal alloys. Overview: Polyetheretherketone (PEEK) is a ketone-based crystalline thermoplastic resin commonly used in dentistry for crowns, implants, fixed partial dentures, and removable partial dentures. This material has high-temperature stability, excellent mechanical properties and chemical resistance, low modulus of elasticity, high solvent resistance, and excellent biocompatibility. Conclusion: PEEK material can be an option to replace metal alloy grips on dentures that are more aesthetic.